Possibilities of the Additional Damping of Unidirectional Fiber Composites by Implementation of Viscoelastic Neoprene and Rubber Layers - Petr Kulhavy; Michal Petru; Martina Syrovatkova (Shock and Vibration)
The aim of the presented work is to assess modal, transmission, and damping characteristics of layered carbon plates. The base is to carry experimental analysis verified by FEM model, which evaluates the vibration transfer of tested composites and describes possibilities of additional damping by implementation of viscoelastic layers. Preimpregnated carbon fibers known as prepreg were used for creation of the samples composed of four (2 constant and 2 variable) layers. The task was to assess impact of changing the fiber orientation on the transfer function and individual modal characteristics. As another option, testing of some additional damping materials was included. Neoprene and thin rubber coat were added as an outside damping element when the neoprene ply was inserted also among the layers. Expected dependence of the plies orientation onto the shape of the transfer function and even swapping of some of MOD characters (bending, torsion, and their combinations) have been found. The use of the additional damping materials is also possible but the right combination of the individual plies layout and stacking sequence is the most significant part. The results had been statistically analyzed and showed that the created layered shell FE models could be used to describe the behavior.